The relationship between spatial configuration and employee sense of community a case study in the offices under DENR Region XI in Davao City - Nituda, Harold Edward S. (2021)
The current spatial configuration for government offices in the country that focuses on cost cutting the budget, hinders the sense of community among the employees during their work hours. This research was conducted to determine how the workplace spatial configuration of a government agency influences the employee sense of community. The offices under the DENR Region XI namely: Survey and Mapping Division (SMD), Community Environment and Natural Resources Office (CENRO) Environment Management Bureau (EMB), Mines and Geosciences Bureau (MGB),and Office of the Regional Director (ORD) are the studied areas for the research.The assessment of the workplace spatial configuration and sense of community is divided mainly into two parts: social and spatial assessment of the studied offices. The social assessment includes the perceived office spatial integration of employees and their sense of community. Perceived office spatial integration includes attributes such as proximity, accessibility, and availability of spaces. Sense of community factors are as follows: fulfillment of needs, membership, influence, and shared emotional connection. Spatial assessment includes the profiling of the space allocation of the studied government offices. Through determining which spatial integration attribute positively influences the employee sense of community, the office architecture may be designed to consider such factors that fosters a sense of community among its employees. Results show that the three attributes of spatial integration namely proximity, accessibility and availability of spaces show a positive correlation on the sense of community of the employees. Out of the three, availability of space was found to have the highest probability of improving the sense of community of the employees. Given that the major concern in government office planning include the inadequate social spaces, aiming to provide a greater space allocation for the employees may become challenging, as the allocated funds to government office infrastructure remain insufficient to provide for the demands of the current government workforce.